Joined Cases C-643/15 and C-647/15 Slovak Republic and Hungary v Council of the European Union - Doliwa-Klepacka, Anna (Polish Review of International and European Law, 2020)
In the commented judgment the Court of Justice has, for the first time, made an analysis of the legal nature of Article 78(3) TFEU including in particular the understanding of the concepts contained in that provision and the conditions for its application. This provision allows the Council to adopt the non-legislative acts in case of a sudden influx of migrants from third countries into the territory of the Member States. The Court also characterized the temporary relocation mechanism as a part of the common asylum system of the EU and a crisis management measure and examined the provisions of Council Decision 2015/1601, obligating the Member States to relocate 120000 persons staying in Italy and Greece – in the light of the notions used in Article 78(3) TFEU.